Non‐invasive prenatal testing for trisomies 21, 18 and 13: clinical experience from 146 958 pregnancies. (8th April 2015) - Zhang, H.; Gao, Y.; Jiang, F.; Fu, M.; Yuan, Y.; Guo, Y.; Zhu, Z.; Lin, M.; Liu, Q.; Tian, Z.; Zhang, H.; Chen, F.; et al.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2015; 45: 512–513 ABSTRACT: Objectives: To report the clinical performance of massively parallel sequencing‐based non‐invasive prenatal testing (NIPT) in detecting trisomies 21, 18 and 13 in over 140 000 clinical samples and to compare its performance in low‐risk and high‐risk pregnancies. Methods: Between 1 January 2012 and 31 August 2013, 147 314 NIPT requests to screen for fetal trisomies 21, 18 and 13 using low‐coverage whole‐genome sequencing of plasma cell‐free DNA were received. The results were validated by karyotyping or follow‐up of clinical outcomes. Results: NIPT was performed and results obtained in 146 958 samples, for which outcome data were available in 112 669 (76.7%). Repeat blood sampling was required in 3213 cases and 145 had test failure. Aneuploidy was confirmed in 720/781 cases positive for trisomy 21, 167/218 cases positive for trisomy 18 and 22/67 cases positive for trisomy 13 on NIPT. Nine false negatives were identified, including six cases of trisomy 21 and three of trisomy 18. The overall sensitivity of NIPT was 99.17%, 98.24% and 100% for trisomies 21, 18 and 13, respectively, and specificity was 99.95%, 99.95% and 99.96% for trisomies 21, 18 and 13, respectively. There was no significant difference in test performance between the 72 382 high‐risk and 40 287 low‐risk subjects (sensitivity, 99.21% vs 98.97% ( P  = 0.82); specificity, 99.95% vs 99.95% ( P  = 0.98)). The major factors contributing to false‐positive and false‐negative NIPT results were maternal copy number variant and fetal/placental mosaicism, but fetal fraction had no effect. Conclusions: Using a stringent protocol, the good performance of NIPT shown by early validation studies can be maintained in large clinical samples. This technique can provide equally high sensitivity and specificity in screening for trisomy 21 in a low‐risk, as compared to high‐risk, population. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.